ASEAN Security Community: Status and Prospects (system-wide analysis) (International relations and international law Journal, 2016)
By the end of the 1990s Association of Southeast Asian Nations (ASEAN) from a purely sub-regional structures has become a real regional association of 10 member states. Different socio-political, constitutional order, cultural heritage and mentality, economic potential and development of the state proved the ability to integrate into the framework of unified international codes of conduct, together known as the «ASEAN Way». But what are the prospects of the organization in the XXI century, taking into account both traditional and new challenges, threats, risks and dangers? This article is devoted to this particular aspect.
Keywords: ASEAN; declaration; regional security; community security; South-East Asia